And the dog rose after death: notes in defense of the other species - Huanca, Jesús (Revista revoluciones, 2021)
It is tragic to see the other species (animals) succumb to the pain of an intentional accident caused by animals (humans), knowing that the indifference of this latter variety is nothing more than pure rencor and selfishness toward itself and the other species. The purpose is to reflect on the inhumanity that is presented in the holders of the greatest rationality without meaning and without brotherhood toward the species that best knows how to show love and fidelity despite not receiving the same thing. That species kept the planet for millions of years because its heart contains no evil, except survival. However, man arrived and changed him to another one full of darkness; today, if the other species dies, it does not matter, for the priority is the infernal legacy that is called: humans. So, the few attempts to reformulate the world will be a challenge for the few who maintain their humanity as the beginning of life.